Effect of Acetaminophen Ingestion on Thermoregulation of Normothermic, Non-febrile Humans - Foster, Josh; Mauger, Alexis; Thomasson, Katie; White, Stephanie; Taylor, Lee (Frontiers in Pharmacology, 2016)
In non-febrile mouse models, high dose acetaminophen administration causes profound hypothermia. However, this potentially hazardous side-effect has not been confirmed in non-febrile humans. Thus, we sought to ascertain whether an acute therapeutic dose (20 mg·kg lean body mass) of acetaminophen would reduce non-febrile human core temperature in a sub-neutral environment. Ten apparently healthy (normal core temperature, no musculoskeletal injury, no evidence of acute illness) Caucasian males participated in a preliminary study (Study one) to determine plasma acetaminophen concentration following oral ingestion of 20 mg·kg lean body mass acetaminophen. Plasma samples (every 20 minutes up to 2-hours post ingestion) were analysed via enzyme linked immunosorbent assay. Thirteen (eight recruited from Study one) apparently healthy Caucasian males participated in Study two, and were passively exposed to 20°C, 40% r.h. for 120 minutes on two occasions in a randomised, repeated measures, crossover design. In a double blind manner, participants ingested acetaminophen (20 mg·kg lean body mass) or a placebo (dextrose) immediately prior to entering the environmental chamber. Rectal temperature, skin temperature, heart rate, and thermal sensation were monitored continuously and recorded every ten minutes. In Study one, the peak concentration of acetaminophen (14 ± 4 µg/ml) in plasma arose between 80 and 100 minutes following oral ingestion. In Study two, acetaminophen ingestion reduced the core temperature of all participants, whereas there was no significant change in core temperature over time in the placebo trial. Mean core temperature was significantly lower in the acetaminophen trial compared with that of a placebo (p < 0.05). The peak reduction in core temperature in the acetaminophen trial was reached at 120 min in six of the thirteen participants, and ranged from 0.1 – 0.39°C (average peak reduction from baseline = 0.19 ± 0.09°C). There was no significant difference in skin temperature, heart rate, or thermal sensation between the acetaminophen and placebo trials (p > 0.05). The results indicate oral acetaminophen reduces core temperature of humans exposed to an environment beneath the thermal neutral zone. These results suggest that acetaminophen may inhibit the thermogenic mechanisms required to regulate core temperature during exposure to sub-neutral environments.